APLIKASI GAME PUZZLE GROW UP BERBASIS ANDROID - Siti Muafiyah; Nurul Fuad; Azza Abidatin Betaliyah (Universitas Islam Lamongan, 2017)
“Puzzle Grow Up” game application uses HTML (Hypertext Markup Language) that can be used on Android-powered devices with the help of Intel xdk program. The purpose of this undergraduate thesis is to learn, analyze, design and implement “Puzzle Grow Up” game application. The software developed in the preparation of this application uses HTML (Hypertext Markup Language) which is the basic language for the web that allows displaying information in the form of text, chart, and also connecting between web pages. The result of this research is to create game as a means of entertainment that can minimize the boredom of a person to the job which involves devices such as mobile phones or smartphones based on Android. The application runs on Android OS with Android Kitkat as the minimum version.